Environmental factors associated with Sarcopenia: a systematic review - Thinakaran Kandayah; Nazarudin Safian; Shamsul Azhar Shah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Elderly is a vulnerable population that is prone for sarcopenia which is associated with the loss of muscle mass, strength and function which are one the diseases that affects elderly. Association between environmental factors with sarcopenia should be explored as it has the potential to influence the health and disability of a person. At present, limited research is conducted to investigate the association which could be attributed to the complex interaction between the human and environmental interactions. Hence this review is conducted to identify the environmental factors associated with sarcopenia. A systematic review was conducted using PubMed, SCOPUS, Web of Science and manual search following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. We used articles that have been written in English and relevant articles were then screened, duplicates were removed, eligibility criteria were applied, and studies that met the criteria were reviewed. The keywords environmental factors, pollutants food environment, neighbourhood environment, locality and sarcopenia were included. Initial search generated 934 publications and 12 articles were included after inclusion and exclusion criteria for this review. In this review, environmental factors associated with sarcopenia are divided into 3 themes that comprises of food environment (availability and physical access, economic access and food quality and safety), neighbourhood environment and pollutants. This systematic review revealed association between the food environment, neighbourhood environment and pollutants with sarcopenia. The findings are salient as it could aid the the policy makers to formulate the necessary strategy to reduce the morbidity and mortality associated with sarcopenia especially with the increase in ageing population globally.